Vicious cycle during chemical degradation of sulfonated aromatic proton exchange membranes in the fuel cell application. (23rd June 2020) - Karimi, Aida; Mirfarsi, Seyed Hesam; Rowshanzamir, Soosan; Beyraghi, Fatemeh; Lester, Daniel
Summary: Weak phase separation and vulnerable linking groups between aromatic units are common setbacks of sulfonated aromatic proton exchange membranes (PEMs) from durability point of view. In this study, sulfonated poly(ether ether ketone) (SPEEK) membranes were exposed to Fenton's solution for a specific time, ranging from 10 to 60 minutes. Chemical structure and morphology evolution, decay in mechanical and thermal stability, and H2 permeability of SPEEK membranes were evaluated during the chemical degradation. Less‐entangled polymeric chains with lower average molecular weight of degraded SPEEK samples diminished mechanical rigidity. In addition, reduction of aromatic rings in each repeat unit led to higher thermal decomposition rate. Furthermore, randomly distributed micro‐defects in the SPEEK morphology and an increase in water sorption can reduce the fatigue strength of membranes in the wet‐dry cycles. Eventually, hydrogen cross‐over rate was gradually increased, and henceforth, accelerated destructive radical formation and degradation can be predicted. Abstract : In this work, new insights into the microstructural evolution and decay in mechanical and thermal stability of SPEEK, as a representative of sulfonated aromatic PEMs, during chemical degradation are provided. H2 cross‐over rate of degraded membranes was gradually increased and it was shown that chemical degradation leaves sulfonated aromatic PEMs in a vicious cycle.